2021
DOI: 10.2147/ccide.s294796
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Extraction of Permanent Teeth in a University Dental Clinic Setting

Abstract: Purpose This study aimed to explore the reasons for tooth extraction and investigated the potential correlations between tooth loss and several variables including age, gender, education level, and other risk factors, such as diabetes and smoking habit. Patients and Methods The study retrospectively analyzed 1811 dental records of patients who underwent extraction procedure of at least one tooth. Patients’ variables included: age, gender, level of education, diabetes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
1
9
0
2
Order By: Relevance
“…Studies exploring the reasons for missing teeth found that dental caries and periodontal disease are the main reasons for tooth mortality, with the former being the more prevalent reason among subjects younger than 40 years of age and the latter in those aged 40 years and above. 4 , 15 Studies conducted on the Saudi population reported that caries was the most common cause of tooth loss, which corroborates with the present study. 13 , 20 Consistent with the literature, this study found that caries was the dominant reason for early loss of all the FPM (100%), and there was no loss of teeth due to periodontal disease or other reasons.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Studies exploring the reasons for missing teeth found that dental caries and periodontal disease are the main reasons for tooth mortality, with the former being the more prevalent reason among subjects younger than 40 years of age and the latter in those aged 40 years and above. 4 , 15 Studies conducted on the Saudi population reported that caries was the most common cause of tooth loss, which corroborates with the present study. 13 , 20 Consistent with the literature, this study found that caries was the dominant reason for early loss of all the FPM (100%), and there was no loss of teeth due to periodontal disease or other reasons.…”
Section: Discussionsupporting
confidence: 92%
“… 2 , 3 First permanent molars (FPMs) are among the earliest erupting permanent teeth in the oral cavity and have been observed as most caries-prone teeth in the mixed dentition. 4 In addition, these teeth are more vulnerable to hypomineralization and periodontal diseases 5 and may result in early tooth loss due to unmet treatment needs. Moreover, FPMs play a crucial part in the development of occlusion and arch integrity, and early loss of these teeth may affect spatial relation, which could significantly affect the symmetry of dentition.…”
Section: Introductionmentioning
confidence: 99%
“…Number of remaining natural teeth is a widely used indicator for oral health as the predominant cause of tooth loss is oral diseases, i.e., caries and periodontitis [ 1 , 2 ]. This indicator is used in epidemiological studies both to investigate oral health [ 3 ] and to explore possible associations between oral conditions and other diseases [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,9,15 Pemahaman mengenai alasan-alasan pencabutan gigi merupakan hal penting untuk meningkatkan kesehatan gigi dan rongga mulut. 2,16 Ketersediaan data mengenai alasan atau indikasi pencabutan gigi di Indonesia masih terbatas.…”
Section: Pendahuluanunclassified